2021
DOI: 10.3390/agronomy11112250
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Effects of Treated Wastewater and Synthetic Fertilizers on Productivity, Energy Characteristics, and Elements Uptake of Potential Energy Crops in an Arid Agro-Ecosystem

Abstract: Using wastewater in agriculture is a desirable alternative source of irrigation and is gaining attraction worldwide. Therefore, this study was designed to assess the effect of treated municipal wastewater (TWW) and groundwater (GW), along with half and full doses of the recommended NPK dose on the plant growth, total biomass, gross energy, and macro- and trace element content and uptake of safflower (Carthamus tinctorius L.), canola (Brassica napus L.), and triticale (X Triticosecale Wittmack) grown in old and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 80 publications
(154 reference statements)
1
7
0
Order By: Relevance
“…In order to cultivate such large areas, millions of tons of synthetic fertilizers are needed to produce high grain yields for rapidly growing populations and their food requirements [3,4]. Nevertheless, the incremental application of synthetic fertilizers can cause harmful impacts on soil organic matter that can consequently result in N deficiency [4], and enhance salt accumulation in soil [5]. In 2018-2019 about 188 Mt was the aggregate world consumption of fertilizers, at a cost of about 155.8 billion dollars; this is expected to grow annually by 3.8% until 2024 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to cultivate such large areas, millions of tons of synthetic fertilizers are needed to produce high grain yields for rapidly growing populations and their food requirements [3,4]. Nevertheless, the incremental application of synthetic fertilizers can cause harmful impacts on soil organic matter that can consequently result in N deficiency [4], and enhance salt accumulation in soil [5]. In 2018-2019 about 188 Mt was the aggregate world consumption of fertilizers, at a cost of about 155.8 billion dollars; this is expected to grow annually by 3.8% until 2024 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium availability may result due to wastewater irrigation, which may correspond to or be in excess to plant necessities [44]. Potassium is involved in many physiobiochemical functions such as the regulation of transportation of stomata in plants [45] and enhances plant tolerance to different stresses such as drought and salinity [8]. Similarly, K is involved in the activation of some enzymes responsible for plant metabolism [46].…”
Section: Discussionmentioning
confidence: 99%
“…The intensive use of nitrogen fertilizer in the agricultural fields directly increases the agricultural production cost. In addition, the application of a large level of nitrogen fertilizer causes a series of environmental problems such as groundwater pollution and soil acidification ( Cameron et al., 2013 ; Iqbal et al., 2020 ; Seleiman et al., 2021 ; Al-Suhaibani et al., 2021 ; Elshayb et al., 2022 ; Shao et al., 2023 ). It has been reported that over-application of N fertilizers has caused significant soil acidification in major Chinese croplands and the soil pH decrease by 0.13 to 2.20 ( Miao et al., 2011 ; Alkharabsheh et al., 2021 ), reasonable nitrogen application can make crop growth better (Gul Roz Khan et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%